Characteristic of Thin Sheet Membrane for a Mechanical Driven Micropump System - Rusli, Mohd Qamarul Arifin; Leow, Pei Ling; Chee, Pei Song; Arsat, Rashidah; Abdul Rahim, Ruzairi (International Journal of Integrated Engineering, 2019)
This paper demonstrates the characteristic of thin sheet membrane for a mechanical driven micropump system by using a spin coater machine. The moving diaphragm material is made from a PDMS prepolymer material. A 100 mm diameter petri dish is used as the mold template for the membrane fabrication. There are three variables that influence the membrane thickness formation during the spin coating process, which are the prepolymer weight, spin coater spinning rate speed and the spinning time. Based on the study, the optimum parameters to fabricate a 300 µm thin sheet membrane by using a 100 mm diameter of petri dish are 2.5 g of prepolymer, 500 rpm of spin coater speed and 180 s of spin time. These parameters yield a thin sheet membrane for the micropump application with 314.82 ± 3.6556 µm thickness.